Євроінтеграція України: цифрові кроки до нового майбутнього - Пивоваров, М. О. (ХНУРЕ, 2024)
Ukraine and the European Union cooperate in the field of digital innovation to support economic growth, increase competitiveness and modernization. Digital technologies such as IT, artificial intelligence, IoT and blockchain play a key role in this process, improving productivity, reducing costs and enabling new areas of business. Cooperation with the EU promotes the exchange of experience and technologies, which increases competitiveness and contributes to stability. Efforts in digital transformation contribute to improving the quality of life of citizens and the efficiency of public administration. Continuation of cooperation in the digital sphere is important for the further development of Ukraine and its position in the international context
Keywords: євроінтеграція України; European Union